Epidemiological Trends and Molecular Characterization of Breast Carcinoma in Erbil, Kurdistan Region of Iraq - Chawsheen, Mahmoud A.; Al-Naqshbandi, Ahmed A.; Ishaac, Rivan H.; Kaka Sur, Fairuz A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
Accumulated evidence suggests a tangible increase in breast cancer (BC) patients in the Kurdistan region of Iraq, yet data on their histological and molecular subtypes remain limited. This study aims to assess the prevalence, histopathologic features, and molecular profiles of BC incidences in Erbil. For this purpose, 261 clinical records of histologically confirmed BC cases from Rizgary Teaching Hospital are analyzed. Results reveal that invasive ductal carcinoma (IDC) emerged as the most frequent histological subtype. In terms of hormonal receptor status, mastectomy patients who tested positive for estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2) are 52.49%, 50.57%, and 18.01%, respectively, and the corresponding figures for Tru-Cut biopsy (TCB) patients are 24.90% for both ER and PR and 6.13% for HER2. Regarding tumor grading, mastectomy patients aged 51–60 have the highest grade II frequency, and TCB patients under 40 years and those between 41 and 50 years show the highest occurrence of the same grade. Moreover, tumor stages II and III made up nearly two-thirds of all cases across all age groups. For the molecular subtypes, luminal A is the most prevalent in both mastectomy and TCB patients. In conclusion, IDC is the predominant BC subtype in the region, with a higher prevalence of ER and PR positivity compared to HER2. Luminal A is the dominant molecular subtype. While stages II and III are common across all ages, tumors of grade II and stage II are frequently observed in older ages.